Perancangan Aplikasi Pembelajaran Iqro’ dan Hukum Tajwid Dengan Metode SDLC - Siti Aisyah Rambe; Khairunnisa; Putri Harliana (SEMINAR NASIONAL TEKNOLOGI INFORMASI & KOMUNIKASI, 2021)
The widespread use of computers, especially in the field of education, is increasing day by day, both users and their uses, This makes multimedia facilities an important supporting tool in all fields, especially in the field of information and communication technology. Along with the development of increasingly sophisticated technology, the development of education must also be more sophisticated. one of them in learning Iqro’ and the law of recitation. Currently, there are still many Muslims who have not been able to read the Qur'an, both children and adults. Iqro 'is a book that contains guidelines for learning the Qur'an in which it is taught how to read good and correct Arabic letters. At this time, Iqro' in book form is still widely used, so it feels less interactive and makes you quickly bored to learn it. Looking at current developments, there is a great need for an Iqro learning application that is even more interesting. Subjected to conventional learning is less effective in its use compared to the media. Media is able to foster children's interest in learning absorption. Therefore, a renewal method is needed in the application of the management of tajwid so that children can more easily understand learning recitation of recitation. The design of the Iqra and Tajweed Law Learning Applications with the SDLC method uses Adobe Flash CS6 software. the results of the design of learning 1qra and the law of recitation with the SDLC method can facilitate children in the process of reading the Qur'an through the iqro' method and the law of recitation.